ÄTA och LOU - Om entreprenadrättsliga ändringar i upphandlade kontrakt - Gruvberger,Marcus (2025)
This thesis examines the extent to which contracting authorities, under the Swedish Public Procurement Act (LOU), may implement contractual changes, additions, and deductions (so called ÄTA works) within the scope of already awarded construction contracts. The issue is particularly relevant since the concept of ÄTA, as defined in the standard contract AB 04, is well-established in the construction industry but does not necessarily align with the requirements imposed by procurement law concerning modification clauses. The analysis focuses on the legal grounds for modifications found in Chapter 17 of LOU, with primary emphasis on 10 § and supplementary provisions in 9, 11, 12, and 14 §§. The review shows that the general and unspecified nature of the ÄTA concept in AB 04, without further clarification or limitation, likely does not meet the criteria set out in 10 §, that such clauses must be clear, precise, and unambiguous. However, other exceptions provided in LOU may, under certain conditions, permit ÄTA works without the need for a new procurement, particularly if the change is of minor value, technically necessary, or caused by unforeseeable circumstances. The thesis also addresses the practical tension between public procurement law and construction contract law, where contracting authorities may, in practice, engage in ÄTA works with a certain degree of procurement law risk taking. It is ultimately suggested that more explicit guidance particularly regarding construction contracts could contribute to a more balanced legal framework that respects both legal certainty and practical flexibility.
Keywords: avtalsrätt; EU-rätt; förvaltningsrätt